A long-term anticorrsive coating through graphene passivation. (November 2018) - Ding, Ji-Heng; Zhao, Hong-Ran; Zheng, Yan; Zhao, Xinpeng; Yu, Hai-Bin
Abstract: Despite graphene (G) is impermeable to all molecules and with excellent chemical stability, conductive G is cathodic to most metals and can aggravate metal corrosion at exposed metal-coatings interfaces. This effect may accelerate dangerous localized corrosion and potentially impedes its applications in metal protection. Here, we present successful synthesis of nonconductive G (FmG) through the Diels-Alder reaction between exfoliated G and a bio-based epoxy monomer, and its application in epoxy (EP) anticorrosive coatings. The FmG as-prepared exhibit well solubility in traditional organic solvents due to the graft of FdE chains on the FmG surface. The corrosion resistances of FmG reinforced EP coatings were investigated by electrochemical tests (open circuit potential, Tafel curves, and impedance) after immersed in a 3.5 wt % NaCl solution. The results demonstrated that embedding 0.5 wt% of FmG in EP coating effectively improves the barrier properties of the coating and shows superior corrosion resistance compared with pure EP. In addition, we also gave the protection mechanisms about the corrosion reaction of G-based modified and unmodified EP coatings. The strategy provides a promise strategy for development of G-based heavy coatings with superior barrier properties for metal protection. Graphical abstract: A reasonable graphene molecular design and its advanced application in improve the corrosion resistance performance of epoxy coatings. Image 1